Primary dengue infection triggered haemophagocytic lymphohistiocytosis in a neonate. Issue 12 (31st December 2020) - Agrawal, Gopal; Wazir, Sanjay; Sachdeva, Anupam; Kumar, Surender
Abstract : Haemophagocytic lymphohistiocytosis (HLH) is an aggressive syndrome which has characteristic symptoms and laboratory findings. Infection is a common trigger of HLH. We report a 2700 g male infant with persistent fever, massive hepatosplenomegaly and severe thrombocytopaenia. Laboratory evidence of primary dengue infection was detected. Investigations revealed hypertriglyceridaemia, hypofibrinogenaemia, hyperferritinaemia and elevated soluble CD25. Bone marrow examination revealed haemophagocytes. The diagnostic criteria for HLH were fulfilled. A diagnosis of secondary HLH triggered by primary dengue infection was considered. Dexamethasone was initiated and continued for 8 weeks. He responded clinically with regression of hepatosplenomegaly, was afebrile and platelet counts normalised. Dengue‐associated HLH is often missed clinically as treating physicians focus more on the underlying infection and its treatment. In neonates, HLH should be considered as differential diagnosis of sepsis and other viral infections, particularly in situations of inappropriate response to standard management.